3D printed titanium carbide MXene-coated polycaprolactone scaffolds for guided neuronal growth and photothermal stimulation - Jianfeng Li; Payam Hashemi; Tianyi Liu; Ka My Dang; Michael G. K. Brunk; Xin Mu; Ali Shaygan Nia; Wesley D. Sacher; Xinliang Feng; Joyce K. S. Poon (Communications Materials, 2024)
Abstract The exploration of neural circuitry is paramount for comprehending the computational mechanisms and physiology of the brain. Despite significant advances in materials and fabrication techniques, controlling neuronal connectivity and response in 3D remains a formidable challenge. Here, we introduce a method for engineering the growth of 3D neural circuits with the capability for optical stimulation. We fabricate bioactive interfaces by melt electrospinning writing (MEW) 3D polycaprolactone (PCL) scaffolds followed by coating with titanium carbide (Ti3C2Tx MXene). Beyond enhancing hydrophilicity, cell adhesion, and electrical conductivity, the Ti3C2Tx MXene coating enables optocapacitance-based neuronal stimulation, induced by localized temperature increases upon illumination. This approach offers a pathway for additive manufacturing of neural tissues endowed with optical control, facilitating functional tissue engineering and neural circuit computation.